2022
DOI: 10.3311/ppci.18647
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Salt Weathering and Water Absorption on the Ultrasonic Pulse Velocities of Highly Porous Limestone

Abstract: One of the major causes of building stone deterioration is salt crystallization. In this study, changes of ultrasonic pulse velocities of highly porous limestone (obtained from the Sóskút quarry, Hungary) during capillary water absorption, water saturation and during salt crystallization tests were investigated. Capillary water absorption and water saturation tests were carried out according to EN 1925 and EN 13755. In salt crystallization test, the samples were submerged in salt solutions of 14 % Na2SO4 (acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…As the castle is situated nearby the coast and is affected by the salt spray effect [35], it was essential to study the stones under NaCl solution. Sulfate salts were used, because Na 2 SO 4 and MgSO 4 are extremely damaging [26][27], and Na 2 SO 4 is considered the most aggressive salt used to assess the durability of the stone in the laboratory [36].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the castle is situated nearby the coast and is affected by the salt spray effect [35], it was essential to study the stones under NaCl solution. Sulfate salts were used, because Na 2 SO 4 and MgSO 4 are extremely damaging [26][27], and Na 2 SO 4 is considered the most aggressive salt used to assess the durability of the stone in the laboratory [36].…”
Section: Methodsmentioning
confidence: 99%
“…However, Rodriguez-Navarro et al [23] do not agree with that argument because they found that environmental conditions (relative humidity and temperature) define which pressure appears and induces damage to the stone. Many different experiments were completed to investigate the effect of salt crystallization on the durability of carbonate stones under various conditions, such as total immersion [24][25][26] or capillary absorption of salt solution [27].…”
Section: Introductionmentioning
confidence: 99%
“…Pulse frequency was 54 Hz in the ultrasonic pulse velocity test. The ultrasonic pulse velocity of the sample was determined using the Equation ( 2) given the length of the wave transmission (sample length) and the recorded transmission times [35]:…”
Section: Ultrasonic Pulse Velocity Testingmentioning
confidence: 99%
“…Deterioration of rocks under the impact of the salt crystallization process has been investigated by many studies (e.g. Khodabandeh and Rozgonyi-Boissinot 2022;Lezzerini et al 2022;Çeli and İbrahimoglu 2021;Çelik and Sert 2020;Benavente et al 2018;Çelik and Tigli 2018;Bozdag et al 2016;Temraz and Khallaf 2016;Barone et al 2015;Ludovico-Marques and Chastre 2012;Akin and Ozsan 2011). However, there is a lack in determining the change in the strength properties regarding abrasion loss value of rocks due to the cyclic salt crystallization process (e.g.…”
Section: Introductionmentioning
confidence: 99%